ALTERNATIVE HISTORY GENRE IN THE FINE LITERATURE. THE ROLE OF EUROPEAN MYTH IN CRYPTOHISTORICAL WRITING - Antonina V. Anistratenko. (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2022)
The article is devoted to the Alternative History (AH) genre in fiction and function of the “European Myth” in cryptohistorical writing. The article aims to determine the identity and path of the alternative historical novel in Ukraine and its comparative characteristics at the current stage of modern fiction. The tasks of the study are to determine the ways of European myth functioning in the artistic space of the neomodern AI novel in Ukraine which creates a new genealogical pattern in Ukrainian literary studies. Research methods are subordinate to the aim of the study and tasks. They are comparative, historicalliterary, descriptive, and analytical methods. The metagenre of alternative history has three key aspects, which seem to determine the comparative level of the American and European literature samples within this genealogical formation. These keys are the following: firstly, the story is supposed to completely match the recorded historical and geographical events up until the bifurcation point (in other words, a classic alternative history cannot be based on cryptohistory, hypothesis, fiction, however its background may be folklore or nation mythological heritage or known ancient culture); secondly, the historical figures should play a leading role in the storyline events, especially in the political context; thirdly, the key storyline is expected to relate to the history of a certain human community or civilization on the planet Earth up to the bifurcation point. Apart from the general experience about a different functional role of the time travel method in alternative history novel, we also have a new update, much more distant from the one declared by M. Schneider-Mayerson in 1995, namely, 1889, the year when M. Twain wrote the novel “A Connecticut Yankee in King Arthur’s Court”. However, the novel by M. Twain was criticized due to its monoculturalism in the political worldview. Although all of these details are related to extraliterary factors. If we compare the invariant of American AH, presented for the first time in the novel by M. Twain, we want to talk about cryptohistory in Ukrainian and Western European literature. In his monograph T. Shippey refers to it as a pseudo-history (’Whig history’). It precedes the novelty of this article, which comes to conclusions about common things in the architectonic structure of the European Myth and cryptohistorical writing. That is why we qualify AH as a metagenre, and the political utopia, cryptohistory, allohistory, uchronia, metahistory, political fantasy novels as AH subgenres. One of the most valuable sources of the article is a set of AH novels by M. Twain, P.W.S. Anderson, S. King, V. Baziv, I. Bilyk, M. Brynykh, V. Vladko, V. Danylenko, R. Ivanenko, R. Ivanychuk, M. Kidruk, S. Protsyuk, V. Shevchuk, Ya. Yanovs’kyi, V. Kozhelyanko. To solve the article’s issues we used comparative and descriptive methods. Conclusions. Every metagenre formation itself has separated into individual genres and varieties during the century and accepted different fable schemes of the other genres, in particular canonical ones, such as historical novel, literary, detective novel, chronicle and fantasy. Cryptohistory is a subgenre of alternative history. In its genealogical formula, the actual story exists only theoretically, while the alternative history that forms the plot after the bifurcation point is based on unproven historical sources. It allows more freedom for the author’s imagination, where they may involve two or more bifurcation points. As previously mentioned, the second point of bifurcation would be based on an unreal story that is presented as a true one. Genre markers and plot schemes are identical to alternative history. Though the goal of reconstructing history disappears and is being replaced by other goals: restoration of national and mental mindset elements (V. Kozhelyanko’s “Ethiopian Sich”), humanization of the society (Kir Bulychov “A Reserve for Academics”), psychologization and/or logical construction of the historical course (H. Garrison`s trilogy “West of Eden”, “Winter in Eden”, “Return to Eden”), etc.